2019
DOI: 10.1155/2019/6370241
|View full text |Cite
|
Sign up to set email alerts
|

Corneal Endothelial Cell Density and Morphology in Healthy Egyptian Eyes

Abstract: Purpose. To evaluate the corneal endothelial cell density and morphology in normal Egyptian eyes. Methods. In total, 568 healthy eyes of 568 Egyptian volunteers aged 20 to 85 years were examined using noncontact specular microscopy for the central corneal thickness (CCT), mean endothelial cell density (MCD), coefficient of variation (CV) in cell area, mean cell area (MCA), and hexagonal cell (Hex) percentage. Variables were compared between sexes and between different age groups. Results. The mean CCT, MCD, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
34
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(46 citation statements)
references
References 32 publications
10
34
1
1
Order By: Relevance
“…In general, the cornea becomes edematous if the CECs decrease or loss of function. This study demonstrated that the CCT decreased with increasing age and this was similar to studies in Lithuania [23], Turkish [13] and Egyptian [14] populations (Table 4). Müller et al investigated the ECD and corneal thickness in different areas of the cornea in elderly eyes using the confocal microscopy and corneal topography (Orbscan II).…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…In general, the cornea becomes edematous if the CECs decrease or loss of function. This study demonstrated that the CCT decreased with increasing age and this was similar to studies in Lithuania [23], Turkish [13] and Egyptian [14] populations (Table 4). Müller et al investigated the ECD and corneal thickness in different areas of the cornea in elderly eyes using the confocal microscopy and corneal topography (Orbscan II).…”
Section: Resultssupporting
confidence: 89%
“…Table 4 The mean ECD in this study was 2732 ± 258 cell/mm 2 , which was similar to the results from other studies using non-contact specular microscope in normal eyes (Table 4). These included Filipino (2798 ± 307) [11], Malay (2648 ± 310) [12], Turkish (2732 ± 307) [13], Egyptian (2647 ± 387) [14], Nigerian (2610 ± 371) [15], and Indian(2525 ± 337) [16]. The mean ECD in Thai eyes was lower than those of Japanese (2943 ± 387) [17] and Chinese (2932 ± 363) [18], but higher than the results of Iranian(1961 ± 457) [19].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The annual endothelial cell loss rate in this study was 0.23%, which was similar to the results in Chinese (0.3%) [18], Indian (0.3%) [16], Egyptian (0.3%) [14], and Japanese (0.25%) [17], while this was lower than those from the Middle East and Caucasians i.e. Iran (0.6%) [19].…”
Section: Resultssupporting
confidence: 87%
“…The mean ECD in this study was 2732 ± 258 cell/mm 2 , which was similar to the results from other studies using non-contact specular microscope in normal eyes (Table 4). These included Filipino (2798 ± 307) [11] , Malay (2648 ± 310) [12], Turkish (2732 ± 307) [13], Egyptian (2647 ± 387) [14],…”
Section: Resultsmentioning
confidence: 99%